Tingkat Pengetahuan Peternak Tentang Manajemen Reproduksi Kambing Lakor di Desa Lolotuara Kecamatan Lakor Kabupaten Maluku Barat Daya - Risart Lewan Dolewikou; Isak Piter Siwa; Harmoko Harmoko; Juwaher Makatita; Jecklin Marlen Lainsamputty (Indonesia Berdaya, 2022)
The purpose of this service is to increase the knowledge and skills of breeders regarding reproductive management of goats in general and measure the ability of farmers to detect estrus and determine mating time before and after parturition through pre-test and post-test evaluations. The method used is the method of socialization (sexual maturity, lust, marriage, pregnancy, birth and weaning, lust and remarriage after parturition); demonstration method (showing and making your own pictures of the cattle mating calendar); Evaluation method (Pre-test and post-test related to the ability to detect lust and determine the right time to mate after parturition). The delivery of material and questions and answers starts from the understanding of reproductive management in its environment including sexual maturity, estrus detection, marriage, pregnancy, birth and weaning and remarriage after giving birth. After that, it was continued with training/practice in which the breeder made and studied the calendar of cattle mating times. This session received a good response because it was seen from the participation and activity of the participants during the process of this activity, both in the delivery of materials and discussions as well as training/practice. Based on the results of the evaluation of the knowledge of farmers about determining estrus detection and determining the timing of remarriage after giving birth before (pre-test) the delivery of material and practice shows that the average knowledge of farmers is in the less category, namely 100%, can only mention 1 answer point. Meanwhile, after the delivery of the material, there was an increase in knowledge of breeders about lust detection, which was in the medium category (57%), the determination of mating time was also in the medium category (60%) which could mention 2-3 points of answers. From the overall evaluation, there was an increase in the knowledge of farmers before and after the delivery of materials and practices so it can be said that this service was achieved according to the expected results.  Abstrak: Tujuan dari pengabdian ini adalah untuk meningkatkan pengetahuan dan ketrampilan peternak tentang manajemen reproduksi ternak kambing secara umum dan mengukur tingkat pengetahuan peternak dalam mendeteksi estrus dan penentuan waktu kawin sebelum dan sesudah partus melalui evaluasi pre test dan post test. Metode yang digunakan adalah metode sosialisasi (dewasa kelamin, birahi, perkawinan, kebuntingan, kelahiran dan penyapihan, birah dan kawin kembali setela partus) ; metode demonstrasi (menunjukan serta membuat sendiri gambar kalender perkawinan ternak); metode Evaluasi (Pre test dan post test terkait kemampuan deteksi birahi dan penentuan waktu kawain yang tepat setelah partus). Penyampaian materi dan tanya jawab dimulai dari pengertian manajemen reproduksi ruang lingkungnya meliputi umur dewasa kelamin, deteksi estrus, perkawinan, kebuntingan, kelahiran dan penyapihan serta kawin kembali setelah beranak. Setelah itu,dilanjutkan dengan pelatihan/praktek yakni peternak membuat dan mempelajari kalender waktu perkawinan ternak. Sesi ini mendapatkan respon yang baik karena dilihat dari keikutsertaan dan keaktifan peserta selama proses kegiatan ini berlangsung, baik dalam penyampaian materi dan diskusi maupun pelatihan/praktek. Berdasarkan hasil evaluasi pengetahuan peternak tentang penentuan deteksi estrus dan penentuan waktu kawin kembali setelah beranak sebelum (pre test) penyampaian materi dan praktek menunjukan bahwa rata - rata pengetahuan peternak berada pada kategori kurang yakni (100%), hanya bisa menyebutkan 1 poin jawaban. Sedangkan setelah penyampaian materi adanya peningkatan pengetahuan peternak tentang deteksi birahi yakni berada pada kategori sedang (57%), penentuan waktu kawin juga berada pada kategori sedang (60 %) yakni dapat menyebutkan 2-3 poit jawaban. Dari keseluruhan Evaluasi, adanya peningkatan pengetahuan peternak sesudah penyampaian materi dan praktek sehingga dapat dikatakan pengabdian ini tercapai sesuai hasil yang diharapkan.